Study problems and depressive symptoms in adolescents during the COVID-19 outbreak: poor parent-child relationship as a vulnerability - Jingyi Wang; Hao Wang; Haijiang Lin; Marcus Richards; Shuyue Yang; Hongbiao Liang; Xiaoxiao Chen; Chaowei Fu (BMC, 2021)
Abstract Background Little is known about the prevalence of and risk factors for adolescent mental health problems during the COVID-19 outbreak. We aimed to investigate the prevalence of depressive symptoms, their association with study-relevant problems, and the moderating effect of parent-child relationship among Chinese adolescents during the school closures. Methods We performed a cross-sectional analysis with data collected in middle and high schools in Taizhou, China. Students completed an online survey between April 16 and May 14, 2020. Depressive symptoms were assessed using the Children's Depression Inventory. Three types of study problems were recorded, including having difficulty in studying at home, dislike of remote learning, and excessive screen entertainment time. Parental relationships were categorized into good or normal relationship and poor relationship. Linear regression and logistic regression analyses were conducted to investigate the associations between study-relevant problems and depressive symptoms. Results Using data from 6435 adolescents, we found that the prevalence of depressive symptoms was 17.7%. All the study problem measures were associated with more severe depressive symptoms. There was a moderating effect of the parental relationship on the associations between study problems and depressive symptoms. The association between number of study problems and depressive symptoms was stronger in adolescents with a poor parent-child relationship (regression coefficient 4.34 [95% CI 2.97, 5.72]) than those with a good or normal relationship (2.55 [2.35, 2.75]), p for interaction 0.002, on multivariable adjustment. Conclusions Study problems due to school closures were particularly problematic for adolescents who had poor parent-child relationships. Public health initiatives could help students to adjust study habits and improve parent-child relationships, thereby protecting against the development of depression.